2005
DOI: 10.1074/jbc.m408237200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of a Divergent CaM Isoform and the Transcription Factor, MYB2, Enhances Salt Tolerance in Arabidopsis

Abstract: Calmodulin (CaM), a ubiquitous calcium-binding protein, regulates diverse cellular functions by modulating the activity of a variety of enzymes and proteins. Plants express numerous CaM isoforms that exhibit differential activation and/or inhibition of CaM-dependent enzymes in vitro. However, the specific biological functions of plant CaM are not well known. In this study, we isolated a cDNA encoding a CaM binding transcription factor, MYB2, that regulates the expression of salt- and dehydration-responsive gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
162
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 268 publications
(170 citation statements)
references
References 48 publications
1
162
0
7
Order By: Relevance
“…The yeast split ubiquitin assay was performed as described previously (Laser et al, 2000;Yoo et al, 2005). Saccharomyces cerevisiae strain JD53 was used for all experiments.…”
Section: Yeast Split Ubiquitin Assaymentioning
confidence: 99%
“…The yeast split ubiquitin assay was performed as described previously (Laser et al, 2000;Yoo et al, 2005). Saccharomyces cerevisiae strain JD53 was used for all experiments.…”
Section: Yeast Split Ubiquitin Assaymentioning
confidence: 99%
“…In plants, certain transcription factors of the basic helix-loop-helix family were shown to bind CaM, thus inhibiting their DNA-binding properties by masking the DNA-binding domain (13)(14)(15). In addition, it was reported that soybean CaM isoforms differentially bind to AtMYB2 and regulate its DNA-binding activity (16). Therefore, interaction of CaM with transcription factors may be a mechanism that transduces Ca 2ϩ signals to the gene expression machinery to induce specific cellular responses.…”
mentioning
confidence: 99%
“…However, in Arabidopsis one of the isoforms of CaM was found to bind to a transcription factor MYB2, enhancing its DNA binding activity. Overexpression of this isoform of CaM in Arabidopsis upregulated the transcription of MYB2 regulated genes including P5CS1, a rate-limiting enzyme in proline biosynthesis (Yoo et al, 2005).…”
Section: Calcium Dependent Signalingmentioning
confidence: 99%